Effects of unilateral versus bilateral plyometric training on endurance running performance - Greenwood, I.; Kay, A.; Baross, A. (International Journal of Strength and Conditioning, 2021)
The purpose of the study was to investigate the effects of an 11-week unilateral versus bilateral plyometric training intervention on maximal isometric voluntary (MVC) knee extensor torque, countermovement jump height (CMJ), running economy (RE) and 3-km time trial (TT) performance. Twenty-seven recreationally trained endurance runners (12 females and 15 males) were randomly assigned to one of three groups: unilateral plyometric training (UPT; n = 9), bilateral plyometric training (BPT; n = 9) and control (CON; n = 9). RE, VO2max, 3-km treadmill TT, isometric MVC (bilateral and unilateral) and CMJ (bilateral and unilateral) were measured prior to and after 11 weeks of training (UPT and BPT; volume equated, 20-40 minutes, 2-3 days/week). Separate two-way repeated measures ANOVAs were used to assess within and between group differences in RE, VO2max, 3-km TT, maximal isometric knee extensor torque and CMJ. Following 11 weeks of plyometric training there were significant improvements in RE (UPT 5.6%; BPT 4.9%, p < 0.01) and 3-km TT performance (UPT 2.4%; BPT 2.5%, p < 0.01) in addition to CMJ (UPT 12.5%; BPT 14.5%, p < 0.01) and maximal isometric knee extensor torque in the unilateral group (14.0%, p < 0.01). No significant differences in VO2max or anthropometric measures were detected (p > 0.05). No statistically significant differences between training interventions (p > 0.05) were detected in any measure. These data demonstrate that UPT and BPT result in similar improvements in RE and 3-km TT run performance in recreational distance runners.